Religião e política em Goiás : uma análise das representações evangélicas na política goiana na Assembleia Legislativa do estado de Goiás entre 2011-2014 - Freitas, Elisa Signates Cintra de (2016)
This paper discusses the relation between politics and religion in the state of Goiás. Due to the high participation perceived in recent years of evangelicals in institutional politics, mainly at the national level, this research intended to confer the presence of this religious group in Goiás, in Goiás State Legislative Assembly in the period of 2011-2014.The state legislators Fabio Sousa (PSDB), Lincoln Tejota (PSD) and Luiz Carlos do Carmo (PMDB) – from the mentioned period - were selected as research subjects. The general objective was to investigate the political activity of the mentioned subjects through five categories: political motivation, church support, religious moral, political activity and laicism. To make this discussion possible, authors such as Max Weber, Jose Casanova, Paul Freston and Joanildo Burity were present throughout this work. Through content analysis of the bills written by the three surveyed evangelical politicians and qualitative interviews with the study subjects, we could perceive in the results the prevalence of secular actions in their political activity in which religious morality was presented as ethics to be daily followed.